2008
DOI: 10.1007/s00415-008-0839-1
|View full text |Cite
|
Sign up to set email alerts
|

Valvular heart disease in patients with Parkinson’s disease treated with pergolide. Course following treatment modifications

Abstract: Compared to controls, aortic regurgitation (OR: 3.1; 95% IC: 1.1-8.8) and mitral regurgitation (OR: 10.7; 95% IC: 2.1-53) were more frequent in PD patients (tricuspid: NS). The number of affected valves (n=2.4+/-0.7) and the sum of regurgitation grades (n=2.8+/-1.09) were higher (p=0.008 and p=0.006, respectively) in the pergolide group. Severity of regurgitation was not correlated with pergolide cumulative dose. A restrictive pattern of valvular regurgitation, suggestive of the role of pergolide, was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
1
5
0
1
Order By: Relevance
“…In our patients at the follow-up assessment a statistically significant improvement of all echocardiographic parameters analyzed has been found, except for AR and PAP. The results of our study are in agreement with those by Dupuy et al [6] who first examined the course of EDA-related valvular damage in a group of 10 PD patients in which pergolide had been suspended for a median period of 13 months, reporting in 60% of them a significant improvement of the mitral valve regurgitation grading and of the sum of regurgitations grading, as well as of number of affected valves. Our findings on valvular regurgitation differ from those published by Rasmussen et al [7], who didn't find any significant change in AR, MR and TR one year after EDA discontinuation, whereas a worsening of these parameters was observed in patients who continued taking the EDA.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our patients at the follow-up assessment a statistically significant improvement of all echocardiographic parameters analyzed has been found, except for AR and PAP. The results of our study are in agreement with those by Dupuy et al [6] who first examined the course of EDA-related valvular damage in a group of 10 PD patients in which pergolide had been suspended for a median period of 13 months, reporting in 60% of them a significant improvement of the mitral valve regurgitation grading and of the sum of regurgitations grading, as well as of number of affected valves. Our findings on valvular regurgitation differ from those published by Rasmussen et al [7], who didn't find any significant change in AR, MR and TR one year after EDA discontinuation, whereas a worsening of these parameters was observed in patients who continued taking the EDA.…”
Section: Discussionsupporting
confidence: 92%
“…In the few followup studies [6][7][8][9], aimed at the assessment of the clinical outcome of VHD, an echocardiographic examination made on average 3 months to about 22 months after EDA withdrawal showed a trend toward a partial regression of VHD, but a complete resolution of the valvular functional and/or morphological damage has not been found. These results are in line with those previously reported with anorectic drugs, such as fenfluramine and dexfenfluramine [14], which share the same mitogenic effect on cardiac valvular fibroblasts and smooth muscle cells, believed to be mediated by stimulation of the 5HT2B receptors family, even though other factors might be involved [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drug dose was not the primary endpoint and was retrospectively acquired that led to inevitable bias [28]. Only a few reports describe the natural evolution of (dex)fenfluramine-and pergolide-induced valvulopathy in a limited number of patients [12][13][14]29]. These studies suggested that VHD was unlikely to progress if the causal drug was removed, and even regression of AR was described in some patients after removal.…”
Section: Discussionmentioning
confidence: 99%
“…Beside dose dependency, reversibility is also topic of interest. Few studies show spontaneous regression of VHD after cessation of the causal drug, but not in all patients [12][13][14].…”
Section: Introductionmentioning
confidence: 99%